2019
DOI: 10.1111/odi.13071
|View full text |Cite
|
Sign up to set email alerts
|

Optical fluorescence imaging in oral cancer and potentially malignant disorders: A systematic review

Abstract: Objectives This study aimed to systematically review the efficacy of direct optical fluorescence imaging as an adjunct to comprehensive oral examination in the clinical evaluation, risk assessment and surgical management of oral cancer and potentially malignant disorders. Methods Studies adopting autofluorescence devices, evaluating the efficacy of comprehensive oral examination and optical fluorescence imaging in detection, visualisation or management of oral squamous cell carcinoma or oral potentially malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 46 publications
(201 reference statements)
0
41
0
Order By: Relevance
“…These include lesion size, site and homogeneity, as well as patient risk factors such as smoking, alcohol use and age . Adjunctive techniques such as tissue autofluorescence can also provide additional information about the malignant potential of specific lesions . Typically however, lesions must be biopsied and submitted for histopathological assessment and the presence and grade of oral epithelial dysplasia (OED) used to assess the risk of MT .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include lesion size, site and homogeneity, as well as patient risk factors such as smoking, alcohol use and age . Adjunctive techniques such as tissue autofluorescence can also provide additional information about the malignant potential of specific lesions . Typically however, lesions must be biopsied and submitted for histopathological assessment and the presence and grade of oral epithelial dysplasia (OED) used to assess the risk of MT .…”
Section: Introductionmentioning
confidence: 99%
“…Typically however, lesions must be biopsied and submitted for histopathological assessment and the presence and grade of oral epithelial dysplasia (OED) used to assess the risk of MT . Higher risk OLK includes those that are larger, non‐homogeneous, exhibit a loss of autofluorescence on imaging and display features of OED, with the risk increasing with the grade . Proliferative verrucous leukoplakia (PVL) is a particularly aggressive variant of OLK characterised by multifocal lesions and a corrugated clinical appearance, and displays a particularly high MT rate of between 40% and 70% …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, VELscope® is an instrument based on the difference between autofluorescence of the normal and dysplastic cells -while fluorochromes of healthy cells react to excitation by emitting light of a specific wavelength that can be visualized using a proper filtration, the distribution of the fluorochromes is disrupted in dysplastic cells resulting in their dark appearance during the investigation. Recent reviews by Nagi et al 8 and Tiwari et al 9 reveal the controversy in using VELscope®, with reported results varying from "not worth doing", through "a valuable adjunctive tool" to "an excellent screening tool". The latest study by Shi et al reported an excellent capability of VELscope® to identify high risk lesions (moderate/severe dysplasia/oral carcinoma) from low risk lesions on a cohort of 517 patients 10 .…”
Section: Discussionmentioning
confidence: 99%